Production Efficiency Analysis of the Hungarian Meat Processing Industry - Berezvai, Zombor (Competitio, 2015)
This paper analyzes the performance of the Hungarian meat processing industry in the wake of the global financial crisis. Between 2011 and 2013 many high-capacity meat processors went bankrupt in Hungary. Possible reasons for that could be unfavorable market situation and inefficiency in production. In this paper, the latter hypothesis is examined. Two different types of production function estimation techniques are used to calculate firm-specific inefficiency estimates. Based on the estimation results, the lower bound of average firm-level efficiency is 0.50, while the upper bound is 0.88. Estimated firm-level inefficiencies are compared to the characteristics of the given firms. Pre-tax profit, company size and domestic ownership are associated with lesser inefficiency. On the other hand, time trend of inefficiencies indicate that the global financial crisis negatively affected the production efficiency of the meat processors. This can be a reason behind the bankruptcies happened.Journal of Economic Literature (JEL) codes: C33, L66